Progress in selective laser sintering using metallic powders: a review. Issue 8 (23rd May 2016) - Singh, S.; Sharma, V. S.; Sachdeva, A.
Abstract : Laser sintering is a newly well established additive manufacturing technique, which has higher capabilities to produce complex shapes models/parts in a short time period. In this technique, a solid model is directly produced according to computer aided design model, by fusing two adjacent layers together, with the interaction of laser light. These parts are widely used in industries like aerospace and automobile and for medical applications as well. This paper reviews the selective laser sintering process and its research progress with the use of metallic powders. The main focus of whole available research progress is to produce complex shape solid model/parts using different metallic materials having the desired mechanical as well as dimensional properties.